Can Larvae of Forest Click Beetles (Coleoptera: Elateridae) Feed on Live Plant Roots? - Kozlov MV; Prosvirov AS; Zvereva EL (MDPI, 2022)
Simple SummaryDetailed natural history information is still lacking for many species of soil-dwelling invertebrates. We asked whether the larvae (wireworms) of two click beetle species, which are most abundant in European boreal forests, feed on live roots of forest plants. The weight of root pieces of downy birch, Scots pine, Norway spruce and wavy hair-grass, offered to wireworms in a laboratory experiment, did not decrease, indicating that these larvae did not consume live root tissues. Therefore, Athous subfuscus and Dalopius marginatus should be excluded from the lists of forest pests damaging tree roots.The life histories of many soil-dwelling invertebrates remain poorly studied. The larvae of two click beetle species, Athous subfuscus and Dalopius marginatus, which are most abundant in European boreal forests, are both classified as omnivorous and are included in lists of root-damaging pests. Nevertheless, we are not aware of any direct proof of their ability (or inability) to consume plant roots. In this study, we asked whether these larvae actually feed on the roots of forest plants in the absence of other food sources. Live roots of boreal forest plants, including trees (Betula pubescens, Picea abies and Pinus sylvestris) and grass (Deschampsia flexuosa), were offered to click beetle larvae in a two-month microcosm experiment. The weight of roots placed in vials with the wireworms did not decrease, indicating that the larvae of these click beetle species did not feed on live roots, even in the absence of other food sources. This suggests that the feeding niches of A. subfuscus and D. marginatus larvae are narrower than previously thought and do not include live plant tissues. Therefore, these click beetle species should be excluded from the lists of forest pests damaging tree roots.